2000
DOI: 10.1017/s0022149x00000317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IgG3 responses to carbohydrates following mouse infection or immunization with six species ofTrichinella

Abstract: The IgG3 antibody responses to carbohydrate epitopes were compared in BALB/c mice infected or immunized with six species ofTrichinella:T. spiralis(T1),T. nativa(T2),T. britovi(T3), T6,T. nelsoni(T7), and T8. The dynamics of IgG3 responses and antigen recognition following infection or immunization were measured by ELISA and Western blot respectively, using glycosylated and deglycosylated larval crude extracts (LCE) prepared from homologous isolates. A high degree of protein glycosylation was found in all speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast, we only observed a slight decrease in the response against IgG3 after O-deglycosylation whereas no bands remained in the western blots. The fact that the IgG3 subclass may recognize glycan epitopes and carbohydrates is well documented (Snapper et al 1992; Dea-Ayuela et al 2000). It has been shown that certain thymus-independent antigens induce the CD5+ populations to undergo an IgG3 class switch (Drabek et al 1997) upon control of Th1 cytokine IFN- γ (Snapper et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we only observed a slight decrease in the response against IgG3 after O-deglycosylation whereas no bands remained in the western blots. The fact that the IgG3 subclass may recognize glycan epitopes and carbohydrates is well documented (Snapper et al 1992; Dea-Ayuela et al 2000). It has been shown that certain thymus-independent antigens induce the CD5+ populations to undergo an IgG3 class switch (Drabek et al 1997) upon control of Th1 cytokine IFN- γ (Snapper et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed consistently that whenever whole-larval extracts are used there is better host protection than when using any isolated parasite antigen, as seen by the reduction in larval or adult worm burden (Behnke et al , 1994; Dea-Ayuela et al , 2000, 2006a, b; Eissa et al , 2003; Deville et al , 2005) (table 1). These responses are within the rage of 50–80% protection in most cases.…”
Section: Vaccine Development Against T Spiralis Infectionmentioning
confidence: 99%
“…These studies have shown increased Th1 (interferon-gamma (IFN-γ)) and Th2 (secretory immunoglobulin A (sIgA)) responses from mesenteric lymph nodes as well as an increase in CD4+ lymphocyte numbers in Peyer's patches (Dea-Ayuela et al , 2006b) and intestinal mastocytosis (Behnke et al , 1994). A number of reports have also shown the activation of systemic immune responses, as indicated by elevated levels of total and specific IgG, IgA, IgM, IgG1, IgE (Th1 response) (Behnke et al , 1994; Goyal et al , 1997; McGuire et al , 2002; Abdel-Rahman et al , 2005; Deville et al , 2005; Dea-Ayuela et al , 2006a, b; Dvorožňáková et al , 2011), IgG2a (Th2 response) (McGuire et al , 2002; Dvorožňáková et al , 2011) and even by the increase of IgG3, a subclass isotype considered as a carbohydrate epitope-associated immunoglobulin (Dea-Ayuela et al , 2000). In spite of their relatively high levels of protection, whole-larval extracts may display some toxicity or immunopathogeny derived from an exacerbated Th2 response, an aspect not yet addressed.…”
Section: Vaccine Development Against T Spiralis Infectionmentioning
confidence: 99%
See 1 more Smart Citation